A foundation monograph of Ipomoea (Convolvulaceae) in the New World - Wood, JRI; Muñoz-Rodríguez, P; Williams, BRM; Scotland,RW (Pensoft Publishers, 2020)
A monograph of the 425 New World species of Ipomoea is presented. All 425 species are described and information is provided on their ecology and distribution, with citations from all countries from which they are reported. Notes are provided on salient characteristics and taxonomic issues related to individual species. A full synonymy is provided and 272 names are lectotypified. An extensive introduction discusses the delimitation and history of Ipomoea arguing that a broad generic concept is the only rational solution in the light of recent phylogenetic advances. Although no formal infrageneric classification is proposed, attention is drawn to the major clades of the genus and several morphologically well-defined clades are discussed including those traditionally treated under the names Arborescens, Batatas, Pharbitis, Calonyction and Quamoclit, sometimes as distinct genera, subgenera, sections or series. Identification keys are provided on a regional basis including multi-entry keys for the main continental blocks. Six species are described as new, Ipomoea nivea J.R.I. Wood & Scotland from Peru, I. apodiensis J.R.I. Wood & Scotland from Brazil, I. calcicola J.R.I. Wood & Scotland, I. pochutlensis J.R.I. Wood & Scotland, I. zacatecana J.R.I. Wood & Scotland and I. ramulosa J.R.I. Wood & Scotland from Mexico, while var. australis of I. cordatotriloba is raised to specific status as I. australis (O’Donell) J.R.I. Wood & P. Muñoz. New subspecies for I. nitida (subsp. krapovickasii J.R.I. Wood & Scotland) and for I. chenopodiifolia (subsp. bellator J.R.I. Wood & Scotland) are described. The status of previously recognized species and varieties is changed so the following new subspecies are recognized: I. amnicola subsp. chiliantha (Hallier f.) J.R.I. Wood & Scotland, I. chenopodiifolia subsp. signata (House) J.R.I. Wood & Scotland, I. orizabensis subsp. collina (House) J.R.I. Wood & Scotland, I. orizabensis subsp. austromexicana (J.A. McDonald) J.R.I. Wood & Scotland, I. orizabensis subsp. novogaliciana (J.A. McDonald) J.R.I. Wood & Scotland, I. setosa subsp. pavonii (Hallier f.) J.R.I. Wood & Scotland, I. setosa subsp. melanotricha (Brandegee) J.R.I. Wood & Scotland, I. setosa subsp. sepacuitensis (Donn. Sm.) J.R.I. Wood & Scotland, I. ternifolia subsp. leptotoma (Torr.) J.R.I. Wood & Scotland. Ipomoea angustata and I. subincana are treated as var. angustata (Brandegee) J.R.I. Wood & Scotland and var. subincana (Choisy) J.R.I. Wood & Scotland of I. barbatisepala and I. brasiliana respectively. Attention is drawn to a number of hitherto poorly recognized phenomena in the genus including a very large radiation centred on the Parana region of South America and another on the Caribbean Islands, a strong trend towards an amphitropical distribution in the New World, the existence of a relatively large number of species with a pantropical distribution and of many species in different clades with storage roots, most of which have never been evaluated for economic purposes. The treatment is illustrated with over 200 figures composed of line drawings and photographs.